Methyl-coenzyme M reductase of Methanobacterium thermoautotrophicum delta H catalyzes the reductive dechlorination of 1,2-dichloroethane to ethylene and chloroethane. - Holliger, C (1992)
Reductive dechlorination of 1,2-dichloroethane (1,2-DCA) to ethylene and chloroethane (CA) by crude cell extracts of Methanobacterium thermoautotrophicum delta H with H2 as the electron donor was stimulated by Mg-ATP. The heterodisulfide of coenzyme M (CoM) and 7-mercaptoheptanoylthreonine phosphate together with Mg-ATP partially inhibited ethylene production but stimulated CA production compared Mg-ATP alone. The pH optimum for the dechlorination was 6.8 (at 60 degrees C). Michaelis-Menten kinetics for initial product formation rates with different 1,2-DCA concentrations indicated the enzymatic character of the dechlorination. Apparent Kms for 1,2-DCA of 89 and 119 microM and Vmaxs of 34 and 20 pmol/min/mg of protein were estimated for ethylene and CA production, respectively. 3-Bromopropanesulfonate, a specific inhibitor for methyl-CoM reductase, completely inhibited dechlorination of 1,2-DCA. Purified methyl-CoM reductase, together with flavin adenine dinucleotide and a crude component A fraction which reduced the nickel of factor F430 in methyl-CoM reductase, converted 1,2-DCA to ethylene and CA with H2 as the electron donor. In this system, methyl-CoM reductase was also able to transform its own inhibitor 2-bromoethanesulfonate to ethylene.